An approach of ensuring interoperability of multi-dimensional data warehouses for monitoring of water resources - Dzemydienė, Dalė; Maskeliūnas, Saulius; Radzevičius, Vytautas (Journal of Environmental Engineering and Landscape Management, 2021)
The realization of really working, on-line system for evaluation of pollution of water processes requires to represent the complexity of such phenomenon. The multi-layered structure of distributed information systems under different responsibilities identify some problems for developing of an adequate decision support system (DSS) working on-line. The aim of this research is to develop the interoperable infrastructure of multi-dimensional data warehouses working on-line for integration of monitoring data, enabling the conditions for more adequate decisions. The design approach includes the constructions of the knowledge base with some layers of representation, including the domain specific ontology, which are needful for evaluation of impacts of water pollution. The results are integrated with the structures of the ISMA database, EuroWaterNet, Water Resource Management Information System – WRMIS, following the requirements of EU Water Framework Directive (2004). The presented results on integration of information sources and collaboration workflows help in searching of suitable indicators for revealing the situations of water pollution from wastewater bodies and can help to retrieve the main objects which influence the monitoring of effluxes in the Baltic Sea.